Repurposing Inhaled Ibuprofenate, a Non Steroidal Anti‐Inflammatory Drug, as a Potential Adjuvant Treatment for Pneumonia, CARDS and its Aetiological Agent SARS‐CoV‐2 - Christian Carlos Zurita‐Lizza; Ignacio Rodriguez‐Sanchez; Pablo Alexis Doreski (Wiley, 2023)
Abstract In this manuscript, we will describe and highlight the most important potential underlying mechanisms of action of the inhaled sodium ibuprofenate in hypertonic saline formulation‐NaIHS aerosolisable, as a probable adjuvant treatment for moderate and severe pneumonia and coronavirus disease 2019 (COVID‐19)‐associated acute respiratory distress syndrome in COVID‐19. In both pathological entities, we will refer exclusively to the pulmonary vasoplegic type and we will describe the following therapeutic effects of NaIHS: anti‐inflammatory, immunomodulatory and antiangiogenic. The synergistic action of these therapeutic effects anti‐inflammatory and immunomodulatory together may exert their action at the pulmonary level through the possible reversal of pulmonary vasoplegia and may thereby restore hypoxic pulmonary vasoconstriction, correcting the uncoupling of the ventilation/perfusion ratio and vasoplegic intrapulmonary shunting and, above all, it may reverse severe hypoxaemia and acute respiratory failure. We will also mention the potential virucidal effects of NaIHS on severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2). There are available three retrospective observational studies in moderate and severe COVID‐19 pneumonia, carried out in Argentina, with all three studies concluding that there was a significant reduction in mortality. The most important of these was conducted with the approval of the Institutional Review Board of the National Bureau of Economic Research of Harvard and Columbia Universities, which analysed data from 5146 patients and concluded that NaIHS reduced mortality by 48.7%, although randomized clinical trials are still needed to confirm these emerging data and enable the rise of NaIHS as a new adjuvant treatment. Conclusively, we deem essential to reuse known drugs, such as ibuprofen, in COVID‐19, due to the constant emergence of variants and subvariants of concern secondary to mutations and immune escape mechanisms of (SARS‐CoV‐2), since effective medical treatments are currently scarce and many of them are controversial or not available worldwide.